2018
DOI: 10.1007/s00128-018-2356-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Determining the Accumulation of Metals: Cu, Zn, Mn and Fe in Tissues of Taraxacum sp. sect. Taraxacum

Abstract: The genus Taraxacum is used in the assessment of soil contamination with heavy metals. There are relatively few studies using sections or species representing this genus. The presented research was conducted in Poland on two habitats, varied in terms of nutrients and metals content. The content of selected metals in leaves and roots of Taraxacum sect. Taraxacum was determined. It was found that in the conditions of increased content of metals in the soil, the analysed species representing sect. Taraxacum accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
4
1
1
Order By: Relevance
“…In both methods, the working electrode was a mercury electrode; it is easy to prepare, and offers sensitive and reproducible results, with fast and simple electrode kinetics [44,46]. Presented in this work voltammetry measurements of Zn, Pb, Cd, Ni and Cu in T. officinale were similar to those obtained by other authors using spectroscopic methods [47][48][49][50][51]. However, samples demonstrated a much higher Cu content than that reported by Habh and co-workers [52].…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…In both methods, the working electrode was a mercury electrode; it is easy to prepare, and offers sensitive and reproducible results, with fast and simple electrode kinetics [44,46]. Presented in this work voltammetry measurements of Zn, Pb, Cd, Ni and Cu in T. officinale were similar to those obtained by other authors using spectroscopic methods [47][48][49][50][51]. However, samples demonstrated a much higher Cu content than that reported by Habh and co-workers [52].…”
Section: Plos Onesupporting
confidence: 74%
“…The presence of slightly elevated Zn levels in soil and dandelion samples collected in Warsaw may reflect the impact of road traffic and power plant emissions [49,55,56]. Literature data indicate strong Zn absorption by plant roots and high mobility inside plant [57]; however, our data only confirm these observations to a certain extent, and only in terms of Zn translocation from roots to leaves (TF1).…”
Section: Plos Onecontrasting
confidence: 61%
“…There are more than three hundred important enzymes in the body, zinc is one of these enzymes [93]. These enzymes play an important role in maintaining body function and natural health, and some of these enzymes also play a role in the process of gene expression [94]. Zinc plays a role in regulating the synthesis of important biological molecules such as blood sugar balance, insulin hormone, glucose transport, body metabolism and its availability in the physiological system.…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…(2014) revealed that urban soils can be a strong indicator of metal contamination levels. The main contributors are human activities, including road congestion, building activity, industrial pollutants, and urban development (Chen et al., 2005; Herath et al., 2018; Królak et al., 2018; Praveena et al., 2018). Heavy metal contamination in urban soil can pose serious health risks.…”
Section: Introductionmentioning
confidence: 99%